Change in practice: a qualitative exploration of midwives' and doctors' views about the introduction of STan monitoring in an Australian hospital - M. E. Mayes; C. Wilkinson; S. Kuah; G. Matthews; D. Turnbull (BMC, 2018)
Abstract Background The present study examines the introduction of an innovation in intrapartum foetal monitoring practice in Australia. ST-Analysis (STan) is a technology that adds information to conventional fetal monitoring (cardiotocography) during labour, with the aim of reducing unnecessary obstetric intervention. Adoption of this technology has been controversial amongst obstetricians and midwives, particularly as its use necessitates a more invasive means of monitoring (a scalp clip), compared to external monitoring from cardiotocography alone. If adoption of this technology is going to be successful, then understanding staff opinions about the implementation of STan in an Australian setting is an important issue for maternity care providers and policy makers. Methods Using a maximum variation purposive sampling method, 18 interviews were conducted with 10 midwives and 8 doctors from the Women's and Children's Hospital, South Australia to explore views about the introduction of the new technology. The data were analysed using Framework Analysis. Results Midwives and doctors indicated four important areas of consideration when introducing STan: 1) philosophy of care; 2) the implementation process including training and education; 3) the existence of research evidence; and 4) attitudes towards the new technology. Views were expressed about the management of change process, the fit of the new technology within the current models of care, the need for ongoing training and the importance of having local evidence. Conclusions These findings, coupled with the general literature about introducing innovation and change, can be used by other centres looking to introduce STan technology.